Testicular Adrenal Rest Tumors in Boys and Young Adults with Congenital Adrenal Hyperplasia - Kim, Mimi S. (J Urol, 2016)
PURPOSE: Testicular adrenal rest tumors (TART) are a well-known complication for males with congenital adrenal hyperplasia (CAH), with potential infertility in adulthood. We assessed the prevalence of TART in infant to young adult males presenting to a CAH Comprehensive Care Center. MATERIALS AND METHODS: 35 males with CAH due to 21-hydroxylase deficiency underwent scrotal ultrasonography (7 males <5 yr, 9 males 5–12 yr, and 19 males >12 yr). There were 32 classical and 3 non-classical CAH. Bone age x-ray (BA) or advanced BA history, glucocorticoid (GC) dose, fludrocortisone (FC) dose, and serum 17-hydroxyprogesterone (17OHP), testosterone, and androstenedione levels within 3 months of the ultrasound were also recorded. RESULTS: TART were detected (TART+) in 5/35 (14%) patients overall: 1/9 (11%) 5–12 yr and 4/19 (21%) >12 yr. TART were not detected in any patients <5 yr, including one infant in poor hormonal control (youngest TART+ was 6.6 yr). All TART+ had bilateral disease and only one had suspicious physical findings. GC dose and 17OHP did not differ between TART+ and TART-. TART+ were more likely to have advanced BA (100% vs. 42%; p= 0.04) and higher FC dose (p< 0.01). All non-classical males were TART-. CONCLUSIONS: TART were present in young males with classical CAH, but not in infants or toddlers. TART were associated with higher FC requirements and history of advanced BA; however, not all poorly controlled males developed TART. Longitudinal studies are needed to understand individual predisposition to TART, and the age at which to begin screening in CAH.